A Prospective Study: Driving After Gastrocnemius Recession. When Is It Safe To Return?. Issue 3 (11th September 2017) - Shah, Ashish; Araoye, Ibukunoluwa; Johannesmeyer, David; de Cesar Netto, Cesar; Jones, Caleb; Stavrinos, Despina
Category: Post-surgical Lifestyle Introduction/Purpose: Gastrocnemius recession is the most common surgical procedure in the foot and ankle orthopaedic community. After surgery, patients ask their surgeons when they can safely resume day-to-day activities such as driving. Most times, the surgeon responds with generalized instructions using pain and patient comfort level as benchmarks for when the patient can return to driving. Several studies have identified safe return times for driving after traumatic injuries. However, a safe return time for gastrocnemius recession patients has never been studied. Given the safety concerns and risk associated with driving after surgery, it is important to have evidence-based advice for patients. The purpose of this study is to determine when a patient can safely return to driving after gastrocnemius recession. Methods: IRB approval has already been obtained for this study. 20 patients undergoing right-sided gastrocnemius recession will be identified in the Foot and Ankle clinic. Inclusion criteria will include first time isolated gastrocnemius recession surgery, licensed driver, and age between 18 and 65. Exclusion criteria will include failure to meet inclusion criteria, inability to return for follow-up testing, non-active driver status, medical contraindication to driving, history of any prior foot and ankle surgeries, and performance of any concurrent foot and ankle surgical procedures alongside gastrocnemius recession. Study participants will attend a driving simulator session prior to undergoing their procedure and will follow-up with repeat simulations at 1, 2, and 4 weeks postoperatively. Collected data will include braking reaction time, total braking time, speed stability, and number of traffic violations. A matched healthy control dataset will be used for comparison. Results: There was no detailed data available at the time of writing this abstract. We anticipate data availability over the next couple of months. Conclusion: We anticipate conclusions on the safe time to resume driving in gastrocnemius recession patients after gathering and processing detailed data. This is the first prospective study to guide counseling for patients undergoing gastrocnemius recession regarding a safe time to resume driving.